The effects of the ethanolic extract of mahogany seeds (Swietenia macrophylla King) on the renal function of streptozotocin-induced diabetic rats - Lukman La Basy; Sri Lestari SR; Sri Kadarsih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2015)
Diabetes-associated oxidative stress causes glomerular hypertrophy, decrease ofglomerular filtration rate and inhibits cell proliferation that lead to the decrease of renalfunction as indiated by the increase of serum creatinine level and the presence ofprotein in urine. Mahogany seed (Swietenia macrophylla King) has been proven to haveantidiabetic activity. This study was conducted to evaluate the effect of the ethanolicextract of mahogany seeds on the renal function of streptozotocin-induced diabetic rats.Six normal rats as control (Group I) and 24 diabetic rats were used in this study. Thediabetic rats were randomized allocated into four groups with six rats in each group.Group II was considered as diabetic rats control and received aquadest. Group III-V wereconsidered as extract administered diabetic group and received ethanolic extract of S.macrophylla seed for 21 days at a dose of 50, 100 and 200 mg/kg BW, respectively.Serum malondialdehyde (MDA), serum creatinine, and urine protein levels were monitored,before and after the ethanolic extract of S. macrophylla seed administration. Serum MDA,serum creatinine and urine protein levels of all rats after STZ induction (Group II-V) weresignificantly higher than without STZ induction (p < 0.05). A significant decrease in theserum MDA and serum creatinine as well as urine protein levels were observed after thetreatment with ethanolic extract of S. macrophylla seed compared to before treatment(p < 0.05). In conclusion, the ethanolic extract of S. macrophylla seed is able to correctrenal dysfunction of streptozotocin-induced diabetic rats.